Iowa Birdline update, April 10-12, 1995 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1995)
Iowa Birdline update for April 10-12, 1995. Highlights of the update include sightings of Smith's Longspurs, a Cinnamon Teal, Sandhill Cranes and a Chestnut-collared Longspur. Also included are handwritten notes for the next week's update with sightings of five Eared Grebes, four Horned Grebes and a Short-eared Owl. Epson - sheet feed/flatbed